The Essence and Concept of Political Islam in a science and History of the Region (Journal of Philosophy Culture and Political Science, 2019)
This article examines the phenomenon of political Islam. In the study of this problem a huge contribution was made by regional and Russian authors. The current situation has shown that researches in this area are considered to be actual. Many authors examine that the problem of domestic terrorism has the impact from the outside. But recent events have shown that our country is in the process of politicization of Islam. The author gave a comparative analysis of different points of view, but it should be noted that related to this phenomenon a negative assessment is given. The author also reviewed the history of the spread of Wahhabism in Central Asia.